A Better Way to Die - Scott Wiper; Argenziano, Carmen; Jack Conley; Kirk McKinney; Matt Gallini; Richard Haje; Rolando Molina; Scott Wiper (USA Newman/Tooley Films, 2000)
Set along the highways of the U.S. heartland, the story follows the journey of an ex-cop who is inadvertently thrust into a fierce struggle between the FBI and the Chicago underworld, both of which are searching for a missing federal agent who holds the key to the syndicate's demise.
A Chicago cop quits the force and finds himself threatened by the Mafia.
Scott Wiper
Language(s): English
Subtitle(s): English, Arabic, Hindi, Turkish
Keywords: Action